2017
DOI: 10.1016/j.niox.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

sFRP4 signalling of apoptosis and angiostasis uses nitric oxide-cGMP-permeability axis of endothelium

Abstract: Nitric oxide (NO) plays a critical role in endothelial functions such as cellular migration, vascular permeability and angiogenesis. Angiogenesis, the formation of new blood vessels from "pre-existing" ones is a carefully regulated process and essential during reproduction, development and wound healing. Previously our lab group reported that Secreted Frizzled-Related Protein 4 (sFRP4) could inhibit angiogenesis in both in vitro and in vivo conditions. sFRP4 belongs to a family of secreted glycoproteins that f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
1
6
0
1
Order By: Relevance
“…HUVEC treated with the sGC inhibitor ODQ showed an increase in apoptosis in EC exposed to DF that was also observed in both HAEC and HUVEC treated with iCRT5, a specific inhibitor of β-catenin transcriptional activity. Our findings are supported by Saran et al 31 who showed that the pro-apoptotic antagonist of Wnt signalling, sFRP4, causes endothelial dysfunction by suppressing NO-cGMP signalling.…”
Section: Discussionsupporting
confidence: 90%
“…HUVEC treated with the sGC inhibitor ODQ showed an increase in apoptosis in EC exposed to DF that was also observed in both HAEC and HUVEC treated with iCRT5, a specific inhibitor of β-catenin transcriptional activity. Our findings are supported by Saran et al 31 who showed that the pro-apoptotic antagonist of Wnt signalling, sFRP4, causes endothelial dysfunction by suppressing NO-cGMP signalling.…”
Section: Discussionsupporting
confidence: 90%
“…This data is consistent with other reports showing that the NO system response acts as an anti-inflammatory agent through inhibition of apoptosis on cells. 36 BPC 157 Promotes Angiogenesis Through NO Response Following Clopidogrel-Induced Gastric Ulcer…”
Section: Bpc 157 Attenuates Clopidogrel-induced Gastric Mucosa Cells mentioning
confidence: 99%
“…In addition, diverse blood cells also contribute to NO availability in the vicinity to endothelium. Dr. Suvro Chatterjee's group at Anna University, Chennai has been investigating NO-cGMP signaling in endothelial permeability, nonalcoholic fatty liver disease (NAFLD), atherosclerosis and during mechanical stresses in RBCs(Balaguru et al, 2016, Nagarajan et al, 2016, Saran et al, 2017, Seth et al, 2017 and are summarizedhere. Rho GTPases downstream effecter, Rho-associated protein kinase (ROCK) isapotential target for cardiovascular diseases.Interestingly, ROCK inhibitorY-27631 was found to modulate NO production in endothelial cells in a biphasic manner suggesting caution for its use in cardiovascular diseases (Kolluru et al, 2014) and advocated a combination therapy of chemotherapeutic drugs and cGMP analogs, which would confer better protection against chemotherapy mediated vascular dysfunctions in cancer patients (Gajalakshmi et al, 2013).…”
Section: Studies On Cardiovascular System and Related Pathological Comentioning
confidence: 99%
“…Secreted Frizzled-Related Protein 4 (sFRP4), a secreted glycoprotein caused endothelial dysfunction followed by suppression of angiogenesis. Saran et al dissected the mechanism of sFRP4 mediated inhibition of angiogenesis that envisaged NO-cGMP signaling and elevated corresponding ROS levels and apoptosis for the induction of endothelial dysfunctions (Saran et al, 2017).…”
Section: Studies On Cardiovascular System and Related Pathological Comentioning
confidence: 99%